Acute and Sub-chronic (28-day) intraperitoneal toxicity studies of the Methanol Root Extract of Securidaca longepedunculata Fresen (Polygalaceae) in Rats. - Y., Haruna (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Despite the wide spread use of Securidaca longepedunculata in all parts of Africa, not much has been reported in the literature about its toxicity. The few reports available are in connection with its trypanocidal and insect toxicity where it is used as a stored grain preservative. In our investigation, it was discovered that intraperitoneal administration (i.p.) of limit dose of 2.83 mg/kg of the extract produced neither mortality nor acute signs of toxicity through out the 48 hours period of observation. In the sub-chronic toxicity study however, i.p. administration of the extract to rats produced dose dependent multiple organ toxicities in the kidneys and the liver. The rats showed signs of respiratory distress and muscle paralysis with a stretching of the hind limbs at the point of death. The extracts also significantly (p<0.05) increased levels of AST and ALT which is diagnostic of hepatocellular damage; in view of the large scale human consumption of this plant even though, LD50 is not a very reliable procedure in the determination of toxicity, however, patients usually combine herbal remedies with orthodox medication or with alcohol often with out the knowledge of the pharmacist or the physician. Considering the potential toxicity of S. longepedunculata, herbal practitioners should be educated on this, especially when the plant is recommended as part of the complex regimen in long term or short term management of chronic illnesses like hypertension and diabetes